Strategi Ibu Tunggal dalam Mendidik Kemandirian pada Anak di Desa Bengkelo-Lor Kecamatan Benjeng Kabupaten Gresik - Sindy Febyanti; Warsono Warsono (Universitas Negeri Surabaya (Unesa), 2023)
The purpose of this study was to describe the strategies used by single mothers regarding efforts to educate children's independence. The focus in this research is the single mother's strategy in educating independence in children, which is related to what mothers do to reduce or eliminate their children's dependence on others. The research approach used is descriptive qualitative. The informants of this study were 5 single mothers. The location of this research is Bengkelo-Lor Village, Benjeng District, Gresik Regency. Data collection techniques used in-depth interviews and participant observation. The data analysis technique uses the Miles and Huberman interactive model. This study uses Edward Lee Thorndike's Behavioristic educational paradigm theory, that single mothers act as intellectual stimuli by carrying out actions and thoughts that will guide children's behavior to become independent. These characters are stimulated by the environment such as by habituation or example to children. Children who catch the stimulus will know and produce behavior in accordance with the goal, namely the character of independence. The results showed that in carrying out independence character education there were four things that single mothers did, including the first, making children as partners in problem solving, positioning themselves as friends with children, sharing shared responsibilities, and using the help of other parties in educating children. . For single mothers in educating the character of independence in children, there are also obstacles or difficulties, this is related to the division of time and also the attitude of the child who feels tired so that it cannot be forced. Keywords: strategy, single mother, independence.